Produção e purificação de penicilina G acilase - Pinotti, Laura Marina (2003)
The main objective of the present work was the study of PGA of B. megaterium production process and purification. The following production aspects were investigated in flasks and/or fermenter: the study of the purity of the culture, the standardization and the conservation of the inoculum, the optimization of the total time of cultivation (germination/propagation and production), the volume of the inoculum, the nutritional requirements of the B. megaterium for the production of the enzyme, the pH, the concentration of dissolved oxygen and the nutrients feeding mode. It was concluded that the conservation of the microorganism in cryovials, in presence the glycerol, showed to be efficient. The germination took 11 hours and the production, 24 hours, which is enough time for the process to reach the maximum production of the enzyme. With respect to the inoculum volume, 3 mL of inoculum/75 mL of medium (108 espores/mL of inoculum), in flasks of 500 mL, were found to be the appropriate conditions for its production. Different sources of carbon and nitrogen were studied and it was verified that glucose, glycerol and concentrations of amino acids above 10.0 g/L repress the synthesis of the enzyme. The largest production of PGA for B. megaterium occurs when the microorganism grows consuming free amino acids, phenylacetic acid (inductor), in the presence of some factor present in the cheese whey. The different components of the cheese whey were investigated and it was verified that none of the macronutrients is responsible for the significant effect of the whey on the production of the enzyme. This work allowed an increase on the enzymatic activities from 56 UI/L and 8,6 UI/g cell, obtained in the first experimental run with the standard inoculum, to 220 UI/L and 65 UI/g cell with the following conditions: 10 g/L of amino acids, 19,6 g/L of cheese whey, 0,4 g/L of salts, 2,7 g/L phenylacetic acid (AFA), initial pH 8,0, absence of pH control, addition of AFA in the beginning of the cultivation and control of dissolved oxygen around 20% of the saturation. During a research stage in Portugal, an investigation on the PGA production by Escherichia coli was also carried out in order to study the technique of adsorption in expanded bed and comparison of the conditions of production of the enzyme for E. coli with those used for B. megaterium. The maximum PGA production using E. coli was 400 UI/L. The same operational conditions used for E. coli were tested for B. megaterium and they didn't result in the enzyme production. In the study of the concentration and purification of the enzyme produced by B. megaterium, the ethanol precipitation technique was optimized. In addition, the ultrafiltration and adsorption in expanded bed (EBA) techniques were also studied. Using ultrafiltration, at 4ºC, enzyme concentrations up to 1541UI/L was reached, without thermal inactivation. The optimization of the previously study conditions results in: flow rate of 0.03 mL/s for the initial 22 mL of ethanol and 0.25 mL/s for the 98 mL of remaining ethanol, with adjustment of the pH of the broth for 6, without the previous dialysis. In the application of the adsorption in expanded bed the dynamic binding capacity found for PGA in clarified broth was about 5 UI / mL of adsorbent, with recovery of 30% of the initial enzyme. A similar value for the dynamic binding capacity was found for PGA of E. coli.